An interesting presentation of pituitary adenoma - M., Banupriya; M., Jagadeesan; I., Mariraj; S., Prasanna Karthik; D., Padmalatha; R., Kannan; J., Damodharan (International Journal of Advances in Medicine, 2019)
Pitutary adenomas are one of the commonest tumors of seller region of which prolactinomas and non- functioning adenomas predominate. The usual presentation are symptoms of endocrine dysfunction and mass effects. We present a case report of 37 year old male presenting with frontal headache and vomiting. Clinical observations revealed frontal bossing with enlarged hands and feet which arose a suspicion of Acromegaly. Investigations revealed elevated IGF 1 (insulin like growth factor) and growth hormone levels. Magnetic resonance image of the brain were done which showed pituitary adenoma. This case highlights the importance of clinical examination and the treating physician must have high clinical index of suspicion to detect endocrine dysfunction and use the modern techniques like stereotactic radio surgery (SRS).